Top 20 of everything - "Igloo" (Igloo Books Northamptonshire, 2011)
Top 20 of Everything by Igloo Books is a fascinating compilation that ranks the world$1 (Bs most intriguing facts, places, people, and phenomena across a variety of topics. From natural wonders and record-breaking achievements to famous inventions and historical landmarks, this book provides readers with lists of the top 20 in each category. Designed to captivate curious minds, each entry is accompanied by colorful illustrations and fun facts, making it a visually engaging experience for readers of all ages. With its wide-ranging topics and appealing format, Top 20 of Everything offers a fun way to explore amazing facts and spark curiosity about the world.s